Factors Influencing Students' Self-Efficacy as the Key to Successful Distance Learning: According to Previous Studies - Dantes, Gede Rasben; Suryandani, Putu Dinia; Suwastini, Ni Komang Arie; Adnyani, Ni Luh Putu Sri; Suarcaya, Putu (Jurnal Penelitian dan Pengembangan Sains dan Humaniora, 2022)
Self-efficacy may be more challenging to achieve in the context of distance learning when students rely on their teachers as their learning source. This study aims to analyze the importance of students' self-efficacy in their distance learning success. This study adapting library research model into the qualitative design, the present study used experts' opinions and previous studies as data sources to answer how students' self-efficacy affects their success in distance learning. Data sources were selected from conceptual and research articles on related topics, published in 2016-2022 in international reputable journals and national journals accredited by SINTA. The selection used specific keywords and a series of inclusion/exclusion processes. Twenty-six articles were included as relevant data sources to answer the research question. Critical readings led to synthesis during the analysis, which resulted in the conclusion that factors affecting self-efficacy, such as familiarity with distance learning, feedback and rewards, motivation and attitude affect students' distance learning success. It implies that metacognitive maturity, such as self-efficacy, plays a vital role in students’ academic success in distance learning.